ASSESSMENT OF PROBIOTIC CHARACTERISTICS OF L.PLANTARUM - SRAVANI KANDULA; RITA NARAYANAN (The Bioscan, 2020)
The present study was conducted to assess the probiotic properties of Lactobacillus plantarum which was obtained from National Collection of Dairy Cultures (NCDC), Karnal, Haryana, for its incorporation in the preparation of a nutraceutical food. Basic identification of Lactobacillus plantarum was done based on phenotypic characters viz., cell morphology, catalase, citrate utilization, tolerance to salinity and carbohydrate fermentation profile. L.plantarum was then screened for probiotic properties like bile tolerance, tolerance to acidity and inhibitory/antimicrobial activity. It was observed that L.plantarum showed tolerance to a maximum bile concentration of 0.6 per cent with cell viability of 8.470±0.015 log10cfu/ml and tolerance to acidity at pH 3 with cell viability of 8.626±0.106 log10cfu/gm. Also, L.plantarum showed maximum antimicrobial activity against Salmonella (zi 3.083±0.040 mm), Staphylococcus aureus (zi 2.200±0.100 mm) and Escherichia coli (zi 1.500±0.025 mm). The results of the present study indicate that Lactobacillus plantarum exhibit probiotic properties and can be concluded to be used as a potential source of probiotic organism in the preparation of nutraceutical foods containing probiotics.